Sustainable synthesis of cobalt nanoparticles for supercapacitor application - Miguel Duarte; Thye Choo; Karina Gonçalves; Daniel Silva; Rubens Faria Junior; Solange Sakata (Brazilian Journal of Radiation Sciences)
The growing demand for renewable energy sources and the continuous increase in global energy demand are responsible for the need to develop new forms of energy storage. In this context, supercapacitors emerged due to properties, such as high charge density, long durability and reduced environmental impact. This work aims to develop electrodes based on cobalt oxide synthesized by ionizing radiation for use in supercapacitors. Synthesis by ionizing radiation consists of a sustainable and ecological approach to the production of nanoparticles, reducing the need for toxic reagents and high temperatures. Cobalt oxide nanoparticles were synthesized by irradiating a solution of cobalt acetate, followed by vacuum filtration and drying. The electrochemical properties of the material were evaluated using cyclic voltammetry in 1 M KOH. The results indicated that the cobalt oxide electrodes have a significant energy storage capacity, indicating their potential for use in supercapacitors.